Using environmental DNA to estimate the seasonal distribution and habitat preferences of a Japanese basket clam in Lake Shinji, Japan. (31st May 2019) - Takahara, Teruhiko; Ikebuchi, Takashi; Doi, Hideyuki; Minamoto, Toshifumi
Abstract: The Japanese basket clam ( Corbicula japonica ) is an economically important food resource for inland estuarine fisheries in Japan. The biomass of C. japonica comprises more than 90% of the total biomass of the macrobenthos in Lake Shinji. However, to manage this resource optimally, knowledge of the seasonal fluctuations of bivalve populations is required. Environmental DNA (eDNA) is increasingly being used to estimate the distribution and biomass of aquatic organisms. We used eDNA to estimate the distribution of a C. japonica population in Lake Shinji, Japan, to elucidate the environmental factors driving its habitat preferences in the lake. The eDNA concentrations of C. japonica along the eastern coast were significantly higher than those on the other coasts of the lake. Furthermore, eDNA concentrations fluctuated seasonally. eDNA concentrations of C. japonica were positively correlated with salinity at sampling sites, suggesting that preferred habitats were associated with salinity. The eDNA method represents a potentially useful monitoring tool, requiring minimal labor and time, to complement or replace conventional bivalve resource surveys and could be useful for the management of the C. japonica fishery. The present study confirmed its utility for estimating the seasonal distribution patterns and habitat preferences of C. japonica in Lake Shinji. Highlights: An environmental DNA (eDNA) assay was used in an estuarine environment in Japan. eDNA was used to estimate distribution of Japanese basket clam, Corbicula japonica. The bivalve's seasonal patterns and habitat preferences were assessed in Lake Shinji. The eDNA concentrations at six sampling stations were correlated with salinity. We confirm that eDNA is a potentially useful tool for monitoring bivalves.